A szőttes aranyszálai: A szimbólumok használatáról a coachingban - Kajtár, Edit (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2020)
Symbols are gold threads in the tapestry of human existence. They appear on cave paintings and smartphone screens, in sacred rituals as well as earthly aspects of everyday life. The writer points out how all coaching schools utilize the power of symbolic thinking, albeit to varying degree. Symbols provide support during the course of the entire coaching process from rapport building through the recognition of the key areas for development, to the elaboration of concrete action steps. Four main areas: the use of images, arts, tales and dreams are analyzed in more details. Symbolic thinking helps us to connect with our true self, with each other as well as the world around us. The writer points out how, why and in what framework do symbols serve as one of the most powerful resources of coaching and personal development.